THREE WAVES OF HOMOSEXUAL EMANCIPATION IN POLAND - Warkocki, Błażej (Porównania, 2014)
The article presents three waves of LGBT emancipation in Poland, as the country of semi-periphery. Therefore, western emancipation is also included in the debate. However, the main goal is to describe emancipation in the terms which have been used by the participants of that process. And from that point of view, the article characterizes the transformation of (the imagined) collective identity. From the 80’s, through the 90’s, but also after 2003. I present how the project of “gay identity” was applied. Polish literature is used here as a mirror of emancipation (from Julian Stryjowski and Marian Pankowski to Michał Witkowski and Paweł Demirski).